A method to improve the accuracy and efficiency for metallized-film capacitor's reliability assessment using joint simulation. (November 2021) - Yin, Jinpeng; Liu, Jinjun; Zhang, Yan; Lv, Chunlin
Abstract: Metallized-film capacitors are widely used in large capacity power electronic equipment to filter the harmonics, buffer the pulsation power and support an operating voltage. However, with the reliability design standard becoming more stringent, the demand to estimate the lifetime more precisely for capacitors surges out. Extracting the hot-spot temperature is the core step, but conventional methods could not fully consider the influence brought by internal and external stresses. Finite element method is more precise but the modification of parameters needs to be done manually, which could be time-consuming. A joint simulation method is then proposed by means of interface between different computer software. This method keeps the advantage of finite element method, taking both the aging of capacitor and the time-varying equivalent resistance into consideration, with the operations being automatically done. Hence the accuracy of hot-spot temperature estimation is improved compared to traditional ways and in the meantime, a more time-efficient reliability evaluation is fulfilled. Highlights: Verified the correctness of the analysis Verified the credibility of the results Rearranged some ambiguous statements Corrected the wrong format of some equations Improved the visual effect of some figures